Investigating the Effect of C-Factor and the Method of Bulk-Fill and Nanohybrid Composites Placement on Their Microtensile Bond Strength to Dentin - Danesh Kazemi AR; Farahat F; Haji Mokhtari M (Shiraz University of Medical Sciences, 2017)
Statement of Problem: Bulk-fill composites have recently been introduced. There are few studies conducted on them. Objectives: Therefore, the aim of this study is to ascertain the effect of C-factor and the method of bulk-fill and nanohybrid composites placement on their microtensile bond strength to dentin. Materials and Method: In this study, 40 extracted third human molars with no caries were collected. The specimens were disinfected and mounted on plaster blocks. Some rectangular cavities (5*3 mm2) were carved on the occlusal level of teeth in the depths of 2 and 4 millimeters. The molars were equally divided into eight study groups at random. After the carving was done, cavities were restored with universal (Tetric N-ceram/Ivoclar vivdent) and bulk-fill (Tetric N-ceram BulkFill/Ivoclar vivdent) composites with incremental and bulky techniques. Then they were stored in distilled water for one week. After that, they were cut into halves from the middle of the restoration spot at the buccolingual direction to turn them into rectangles. Then the microtensile bond strength test was carried out on them to record the failure resistance. The data were analyzed by conducting an ANOVA, a post hoc test, and a T-test. The failure mode was evaluated with a stereomicroscope. Results: Using bulk-fill and nanohybrid composites in cavities filled mas-sively in a 4-mm depth showed a significantly lower level of microtensile bond strength compared with other groups (p= 0.000). Failure was often adhesive in these groups. Conclusion: Considering the research constraints of this laboratory study, bulk-fill composites can be cured well in a 4-mm depth. However, it is advised to use the incremental method in cavities with high C-factors due to the high stress caused by the polymerization shrinkage.